Verbal humour in primary school children: Development of metapragmatic awareness - Larissa Timofeeva (Feminismo/s, 2014)
This paper focuses on some aspects of humour acquisition, based on the analysis of humorous narratives written in Spanish by 9-10-year-old schoolchildren. The analysis is supported by three main ideas. Firstly, the debate about gender differences of humour processing becomes especially interesting in the case of children due to their less cultural and social «contamination». Secondly, an important lack of linguistic studies about children’s humour is revealed since the main body of research is of developmental psychology. Thirdly, the age period analysed in this paper is one of the most important in linguistic and, especially, metalinguistic development of children.